Uso de laboratório virtual e de metodologias diversificadas no ensino de biologia celular - Leal, Aline Jaime (2018)
Practical activities in the teaching of Science are related to the development of skills and abilities related to doing Science, such as: observation, identification, proposition of hypotheses and argumentation. In the current scenario, these activities are not restricted only to face-to-face laboratories (PLs) existing in schools, since they can also be performed by remote and virtual laboratories through the Internet. The three types of laboratories have potentialities and limitations, but they do not overlap in terms of skills and competences development, and the combined use of the three types of laboratories is ideal. In this work, it was used color content, with an approach to elementary education, as a way to demonstrate that it is possible to use the three types of laboratories combined. Virtual learning labs (LVAs) have been used successfully in teaching science in the last decades. However, there is a shortage of this resource for the Basic Education, since the majority is destined to students of Higher Education. After analyzing scientific articles between 2001 and 2015, we verified that a virtual laboratory needs to have some characteristics to support the teaching and learning process of sciences, such as: present the theoretical content in a clear and succinct way; be easy to use in order to promote the digital inclusion of its users; be attractive and interactive to awaken interest and motivation of the students, as well as to enable communication between their users and present several methodologies to evaluate the students' learning process. Based on the above, the Virtual Laboratory of Cell Biology (LVBC) was developed from a constructivist perspective, addressing the contents: cell types, genetic material and cell division. The LVBC promoted the learning of students of Integrated High School, when applied with LP and traditional theoretical classes and was well evaluated by its users (students and teacher regent). The sections and content preferred by the LVBC students were: the animation, the interactive table, the simulators, the practical classes and the glossary. The activities of argument construction and justification in written form were those that the students presented greater difficulty and lower performance. The use of mental maps as mediators for the theoretical study in the LVBC was efficient, both for introduction and review of the content, the same was verified with the dramatization of mitosis.